Role of Law in Social Transformation : Current Issue and Challenges - Dr. Kunal Shaktawat, (International Journal of Scientific Research in Science and Technology, 2024)
Law and Social transformation is a very unique concept which highlights the studies and changes in social problems and their solutions through legal approach. Here law changes the society which means that the law of the land compels the society to be changed according to law. When dispute arises matter is brought before the judiciary which applies the rule of law principle to change either the existing custom or law. Secondly society changes the law it means that the law is made by the society according to the requirement of the democratic institution. It can be brought out either by legislating function or by adopting customs and practices. Law has always be seen as an instrument that could bring out social change. An attempt is made in this paper to emphasize that though there are several devices to bring about a change and transformation in our society but for law none can be considered as the most effective and safest method.
Keywords: Unique; Social Transformation; Society; Rule of Law; Judiciary; Customs and Practices